1997
DOI: 10.1016/s0092-8674(00)80180-4
|View full text |Cite
|
Sign up to set email alerts
|

The RNA–DNA Hybrid Maintains the Register of Transcription by Preventing Backtracking of RNA Polymerase

Abstract: An 8-9 bp RNA-DNA hybrid in the transcription elongation complex is essential for keeping the RNA 3' terminus engaged with the active site of E. coli RNA polymerase (RNAP). Destabilization of the hybrid leads to detachment of the transcript terminus, RNAP backtracking, and shifting of the hybrid upstream. Eventually, the exposed 3' segment of RNA can be removed through transcript cleavage. At certain sites, cycles of unwinding-rewinding of the hybrid are coupled to reverse-forward sliding of the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
433
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 420 publications
(459 citation statements)
references
References 44 publications
21
433
1
1
Order By: Relevance
“…32, whereas the RNA-RNA (folding) contribution is obtained from the VIENNARNA package (33). The number of hypertranslocated configurations is bounded by the length of the hybrid, whereas the backtracked ones are fixed at 9, to account for paused complexes known to backtrack by Ͼ6 nt (36). Increasing backtracking beyond 9 nt does not affect our results in the presence of RNA folding (see below).…”
Section: Statistical Mechanics Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…32, whereas the RNA-RNA (folding) contribution is obtained from the VIENNARNA package (33). The number of hypertranslocated configurations is bounded by the length of the hybrid, whereas the backtracked ones are fixed at 9, to account for paused complexes known to backtrack by Ͼ6 nt (36). Increasing backtracking beyond 9 nt does not affect our results in the presence of RNA folding (see below).…”
Section: Statistical Mechanics Approachmentioning
confidence: 99%
“…[Note that, as in the gel experiments used to identify transcriptional pauses (36)(37)(38), a pause site refers to the transcript length for which pausing occurs, without reference to the precise backtracked position along the template.] The cutoff parameter, (0 Ͻ Ͻ 1), is determined by optimizing the statistical significance of our predictions over all experimental templates.…”
Section: Statistical Mechanics Approachmentioning
confidence: 99%
“…After misincorporation, the mismatched nucleotide at position +1 of the RNA is frayed away from the template, thereby pausing RNAP. Pausing is the first step in backtracking [63,[76][77][78][79][80][81][82][83]. The frayed nucleotide then inhibits RNA extension, because it prevents NTP binding, but favors backtracking, because the bp in position +1 is disrupted.…”
Section: Model For Transcriptional Proofreadingmentioning
confidence: 99%
“…Although efficient cleavage occurs in vitro only in the presence of a stimulatory factor, hydrolytic transcript cleavage is an intrinsic activity of the RNAP (Orlova et al 1994;Rudd et al 1994) and is believed to be promoted by the RNAP active center (Rudd et al 1994). The active center can approach the scissile phosphodiester bond by upstream sliding of RNAP along the transcript (Komissarova and Kashlev 1997;Nudler et al 1997), as shown in Figure 7, structure III (the endonucleolysis-ready form). Structure III is incapable of transcript elongation.…”
Section: Structure and Properties Of A Transcription Elongation Complexmentioning
confidence: 99%